Rise! : from caged bird to poet of the people, Maya Angelou - Hegedus, Bethany (Lee & Low Books Inc., 2019)
Picture book celebrating the life of writer, performer, poet, activist, and humanitarian Maya Angelou. Highlights the origins of her love of reading, her work with Dr. Martin Luther King Jr. and Malcolm X, and how she became famous in her own right as a poet.